Pesan Moral pada Film Mencari Hilal: Analisis Semiotika Roland Barthes - Elvina Juniatri; Sururuddin; Mila Wahyuni (Islamic Journalism Department/ Program Studi Jurnalistik Islam, 2022)
Film is one of the mass communication media which is very effective in conveying moral messages to the public. As a visual communication medium, films use moving images and audio which contain information to the audience. Movies become entertainment shows and guidance. In this research, the writer chose the film